Implication of inflammatory cytokines in the aqueous humour for management of macular diseases. Issue 3 (18th September 2019) - Yi, Quan‐Yong; Wang, Yan‐Yan; Chen, Li‐Shuang; Li, Wen‐Die; Shen, Yu; Jin, Yuanhui; Yang, Jie; Wang, Yuwen; Yuan, Jianshu; Cheng, Lingyun
Abstract: Purpose: To characterize profile of cytokines in aqueous humour of common macular diseases during intravitreal anti‐VEGF therapy. Methods: Aqueous humour from eyes with central retinal vein occlusion (CRVO), branch retinal vein occlusion (BRVO), diabetic macular oedema (DME), neovascular age‐related macular degeneration (nAMD) or pathologic myopia associated choroidal neovascularization (pmCNV) was sampled prior to 1st ( n  = 144) and 2nd ( n  = 48) intravitreal anti‐VEGF therapy. Cytokines including vascular endothelium growth factor (VEGF), intercellular adhesion molecule 1 (ICAM‐1) and interleukin 6 (IL‐6) were quantitated and analysed along with retinal thickness data by optical coherence tomography (OCT) across two intravitreal injections and five macular disease types. Results: ICAM‐1, IL‐6 and VEGF are positively associated in the aqueous humour of naive eyes ( r  = 0.39–0.77, p = 0.018 to <0.0001). ICAM‐1, VEGF and IL‐6 were significantly higher in CRVO and DME while lowest in pmCNV (p < 0.0001). Reduction of central retinal thickness (CRT) as a favourable response to anti‐VEGF therapy was in the order of CRVO, BRVO, DME and nAMD/pmCNV (p < 0.0001). The strongest predictor for favourable CRT reduction was baseline CRT (p < 0.0001) followed by baseline ICAM‐1 (p = 0.04). After the 1st intravitreal anti‐VEGF therapy, VEGF in aqueous humour lowered significantly but ICAM‐1 and IL‐6 levels remained unchanged. ICAM‐1 was not predictive for CRT reduction following 2nd anti‐VEGF therapy. Conclusion: Rate of cytokine production is disease‐dependent and higher in CRVO and DME. Anatomical response to intravitreal anti‐VEGF therapy is disease‐specific and best in RVO patients. A combination therapy using both anti‐VEGF and anti‐inflammatory therapeutics may be superior to single anti‐VEGF therapy, at least for RVO and DME.